2010
DOI: 10.1243/09544062jmes1917
|View full text |Cite
|
Sign up to set email alerts
|

Force sensing and its application in minimally invasive surgery and therapy: A survey

Abstract: The reduced access conditions of minimally invasive surgery and therapy (MIST) impair or completely eliminate the feel of tool—tissue interaction forces. Many researchers have been working actively on the development of force sensors and sensing techniques to address this problem. The goal of this survey article is to summarize the state of the art in force sensing techniques for medical interventions in order to identify existing limitations and future directions. A literature search was performed from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 100 publications
(118 reference statements)
0
118
0
Order By: Relevance
“…The design and implementation of force/moment sensors to be used during surgical interventions had to fulfill the operating workspace constraints, electrical safety, sterilization and biocompatibility [16,22] issues. Forces and moments were estimated after a calibration procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and implementation of force/moment sensors to be used during surgical interventions had to fulfill the operating workspace constraints, electrical safety, sterilization and biocompatibility [16,22] issues. Forces and moments were estimated after a calibration procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible technologies for six axes forcemoment sensors design (e.g., piezoresistive, piezoelectric, capacitive etc. [3,12,22]), SGs allow for easy customization, guarantee wide design possibilities and are costeffective.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method of sterilization is applying saturated steam on the instruments for a duration of about 15 minutes [74]. Therefore, the sensors must be robust to heat, pressure and humidity.…”
Section: B Force and Tactile Sensingmentioning
confidence: 99%
“…However, limited flexibility of some optical fibers and sensitivity to changes in light intensity caused by tilting of the optical cables or misalignment limits their use. Trejos et al [74] summarized the MIS force sensing methods available in the literature until July 2009. Recent works on miniature force sensor for Robot-assisted Minimally Invasive Surgery (RMIS) applications have proposed innovative designs to achieve structural simplicity and potential cost effectiveness.…”
Section: ) Force Measurement Systemsmentioning
confidence: 99%
“…One approach to overcoming this problem is the placement of strain/force sensing transducers either onto the instrument tip or as close as possible to it. Many research groups have indicated that the ideal location for force sensor placement is as close as possible to the site of interaction [2,[8][9][10][11][12], which for MIRS is at the instrument tip. This is technically the most challenging location for placement of a force transducer owing to space limitations.…”
Section: Introductionmentioning
confidence: 99%